The compliance of routine hand hygiene among nurses and midwives at Tra Vinh Hospital of Obstetrics, Gynecology and Pediatrics in 2020 and associated factors (Vietnam Journal of Community Medicine, 2021)
Objective: The study described the routine hand hygiene of nurses and midwives at Tra Vinh Hospital of Obstetrics, Gynecology and Pediatrics in the year 2020 and some associated factors.Method: This was a cross sectional study. Totally, there were 360 chances of hand hygiene to be observed using a checklist. Data was analyzied by SPSS software version 20.0. Chi square test and odd ratios were applied with significant level at 0.05.Results: The prevalence of routine hand hygiene compliance was 33.3% by chances of hand hygiene, and was 30.3% by nurses and midwives. The highest prevalence of compliance was “After contact with patients” (55.5%) and the lowest prevalence was “After contact with blood and fluids”. Some factors associated with the compliance of routine hand hygiene among nurses and midwives were the availability of hand rubs, facilities supporting hand hygiene compliance, workload, rewards and punishments for the compliance of routine hand hygiene.Conclusion: There is a need to retrain routine hand hygiene for nurses and midwives. Supervision of the compliance of routine hand hygiene needs to be conducted, especially for Departments of Obstetrics, Department of Pediatrics, and Department of Surgical Obstetrics.